Accuracy of sonographic fetal weight estimation: influence of the scan-to-delivery interval in combination with the applied weight estimation formula - Faschingbauer, Florian; Raabe, E.; Heimrich, J.; Faschingbauer, Cornelia; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Kehl, Sven (Archives of Gynecology and Obstetrics, 2016)
To evaluate the influence of the time interval between examination and delivery on the accuracy of sonographic fetal weight estimation (WE).8723 singleton pregnancies were included in this retrospective cohort study. Fetuses were divided into eight groups with regard to the time interval between estimation and delivery (group 1: 0 days; group 2: 1-3 days; group 3: 4-7 days; group 4: 8-14 days; group 5: 15-21 days; group 6: 22-28 days; group 7: 29-35 days; group 8: 36-42 days). The accuracy of WE was compared between the different time interval groups and five commonly used formulas using means of percentage errors (MPE), medians of absolute percentage errors, and proportions of estimates within 10 % of actual birth weight.In group one, the Hadlock I and Warsof formula showed a systematic underestimation of fetal weight (negative MPEs). No systematic error was found with the Hadlock II formula and the equations of Merz and Shepard showed a systematic overestimation (positive MPEs). MPE values of the Hadlock I, II and Warsof formulas were closest to zero in WEs of group two. From group three to six, MPE values decreased continuously. With the Merz and Shepard equations MPEs were closest to zero in group four.The best accuracy of sonographic WE with most of the commonly used equations is achieved within a scan-to-delivery interval of 1 week.
EVALuna2:5556

Implementation and Feasibility of Electronic Patient-Reported Outcome (ePRO) Data Entry in the PRAEGNANT Real-Time Advanced and Metastatic Breast Cancer Registry - Wallwiener, Markus; Heindl, Felix; Brucker, Sara Y.; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer.As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three standardized Internet-based questionnaires (EQ 5D 5 L, CES-D and IPAQ). Feasibility was assessed by the staff members who assigned the user accounts by the patients. The completeness of the questionnaires was also assessed.Fifteen of 17 patients who were asked agreed to participate to complete the PRO questionnaires (EQ-5D-5L and CES-D). However, the IPAQ (physical activity) questionnaire was only validly completed by 9 patients. Feasibility was ranked better by the physicians and dedicated clinical trial staff than by the nursing staff.Incorporating ePRO questionnaires into an advanced breast cancer registry is feasible, and no major hurdles were reported. Involving stakeholders from the start, the application is tailored to the capacities and abilities of both patients and clinical staff. The patients' compliance was better with some questionnaires, but others may present difficulties.
EVALuna2:176

Intrapartum sonographic weight estimation - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Schild, R. L.; Beckmann, Matthias; Kehl, Sven; Mayr, Andreas (Archives of Gynecology and Obstetrics, 2015)
To evaluate the accuracy of intrapartum sonographic weight estimation (WE).This retrospective, cross-sectional study included 1958 singleton pregnancies. Inclusion criteria were singleton pregnancy with cephalic presentation, vaginal delivery and ultrasound examination with complete biometric parameters performed on the day of delivery during the latent or active phase of labor, and absence of chromosomal or structural anomalies. The accuracy of intrapartum WE was compared to a control group of fetuses delivered by primary cesarean section at our perinatal center and an ultrasound examination with complete biometric parameters performed within 3 days before delivery (n = 392). Otherwise, the same inclusion criteria as in the study group were applied. The accuracy of WE was compared between five commonly applied formulas using means of percentage errors (MPE), medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.In the whole study group, all equations showed a systematic underestimation of fetal weight (negative MPEs). Overall, best MAPE and MPE values were found with the Hadlock II formula, using BPD, AC and FL as biometric parameters (Hadlock II, MPE: -1.28; MAPE: 6.52). MPEs differed significantly between WE in the study and control group for all evaluated formulas: in the control group, either no systematic error (Hadlock III, IV and V) or a significant overestimation (Hadlock I, II) was found. Regarding MAPEs, application of the Hadlock III (HC, AC, FL) and V (AC) formula resulted in significant lower values in the control group (Hadlock III, MAPE: 7.48 vs. 5.95, p = 0.0008 and Hadlock V, MAPE: 8.79 vs. 7.52, p = 0.0085). No significant differences were found for the other equations.A systematic underestimation of fetal weight has to be taken into account in sonographic WE performed intrapartum. Overall, the best results can be achieved with WE formulas using the BPD as the only head measurement.
EVALuna2:5506

Sonographic weight estimation in fetal macrosomia: influence of the time interval between estimation and delivery - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Kehl, Sven (Archives of Gynecology and Obstetrics, 2015)
To evaluate the influence of the time interval between examination and delivery on the accuracy of sonographic weight estimation (WE) in fetal macrosomia.896 singleton pregnancies (birth weight > 4,000 g) with a total of 1,281 sonographic weight estimations were included in this retrospective cohort study. Fetuses were divided into six groups with regard to the time interval between estimation and delivery: group 1: scan-to-delivery interval: 0 days; group 2: scan-to-delivery interval: 1-3 days; group 3: scan-to-delivery interval: 4-7 days; group 4: scan-to-delivery interval: 8-14 days; group 5: scan-to-delivery interval: 15-21 days; group 6: scan-to-delivery interval: 22-42 days. The accuracy of WE was compared between five commonly used formulas using means of percentage errors (MPE), random error, medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.Significant differences were found between the time interval groups with regard to MAPE and MPE values (p < 0.001). All formulas showed a systematic underestimation of fetal weight (negative MPEs) (p < 0.05). MPE values were closest to zero in time interval group 1 and 2. From group 3 to 6, a continuous decrease was observed. The lowest MAPE was found with the Merz formula in group 1 and 2. Values increased continuously from group 3 to 6. Differences between time interval group one and three did not reach statistical significance.WE in fetal macrosomia shows the best results when examinations are performed within 7 days before delivery, using the formula of Merz et al. Accuracy significantly decreases after this time period.
EVALuna2:5469